Ozaeta-Fidalgo: MADRID. - Cohn, David (Architectural Record, 2025)
The article focuses on the architectural practice of Arantza Ozaeta and Álvaro M. Fidalgo, who have developed a collaborative and adaptive approach to design in response to the economic crisis in Spain. Graduates of Madrid’s Polytechnic School of Architecture, they emphasize nonhierarchical decision-making processes that involve clients and communities, as demonstrated in projects like the Childcare Center in Selb and the POP-UP House. Their work reflects a commitment to flexibility and future adaptability, as seen in their designs for a Youth Hostel that was later converted into a shelter for Syrian refugees. Ozaeta and Fidalgo also collaborate with other professionals to enhance their capabilities and address complex projects, embodying a networked approach that challenges traditional architectural practices.